Beobachtungen zur periglazialen Höhenstufe in den Hochgebirgen von Papua New Guinea - Löffler, Ernst (ERDKUNDE, 1975)
Periglacial phenomena like solifluction terraces and patterned ground are not widespread or conspicuous in the mountains of Papua New Guinea. The delineation of their altitudinal zonation seems however important to allow regional comparisons particularly with other tropical areas. Terraces with vertical, slightly overhanging faces occur on the highest mountains from about 4000-4100 m. They are widespread above 4200 m an altitude substantially only exceeded by Mt. Wilhelm (4509 m). Features of free solifluction like patterned ground and unvegetated terraced solifluction screes are present above 4350 m but their occurrence is relatively restricted because of the predominance of rock faces. Comparison with high mountains of tropical East Africa shows that in the highly humid quasi-oceanic mountains of Papua New Guinea, the upper forest limit is considerably higher, the lower limit of periglaeial activity and the lower limit of free solifluction are slightly higher and the snowline clearly lower than on the mountains of East Africa in com parable latitudes. The lower limits of forest, periglaeial activity and free solifluction on East African mountains are thought to be primarily due to the more continental type of climate with its more pronounced daily temperature amplitude, while the higher snowlines are clearly due to the lower precipitation which in contrast to Papua New Guinea decreases rapidly with increasing altitude.